1999
DOI: 10.1002/(sici)1097-0088(199907)19:9<1011::aid-joc411>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between height to width ratios and the heat island intensity at 22:00 h for Singapore

Abstract: The statistical relationship between urban canyon height-to-width (H/W) ratios and nocturnal heat island intensities for public housing estates in Singapore has been examined. Although a number of similar studies have been conducted for temperate cities, this is a first attempt at correlating H/W to heat island intensities for a tropical city. Heat island intensities were examined specifically at 22:00 h because a previous study of Singapore's heat island determined that the heat islands were well developed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 11 publications
(21 reference statements)
1
27
0
2
Order By: Relevance
“…The section on Urban Heat Island Studies below provides a more detailed review and synthesis of some of the work including older studies. Locations of recent UHI studies include in (1) equatorial wet climates Singapore (Tso, 1996;Nicol, 1996Nicol, , 1998Goh and Chang, 1999;Chow and Roth, 2006); Kuala Lumpur (Tso, 1996), (2) tropical wet/dry climates Bangkok, Manila, Ho Chi Minh City (Hung et al, 2006), Mumbai (Kumar et al, 2001), Puerto Rico (Gonzalez et al, 2005;Velazquez-Lozada et al, 2006), (3) tropical highland climates Mexico City (Jauregui, 1997(Jauregui, , 2005Jauregui and Luyando, 1998), Guadalajara (Tereshchenko and Filonov, 2001), (4) subtropical humid climates Shanghai (Ding et al, 2002;Chen et al, 2003b), Hong Kong (Giridharan et al, 2004(Giridharan et al, , 2005Nicol and Wong, 2005) and Buenos Aires (Figuerola and Mazzeo, 1998;Bejaran and Camilloni, 2003) and (5) subtropical dry climates Pune (Deosthali, 2000), Tuscon (Comrie, 2000), Phoenix (Brazel et al, 2000;Hawkins et al, 2004 andFast et al, 2005), Cairo (Rooba, 2003), Ouagadougou (Linden, 2004) and Eilat (Sofer and Potchter, 2006). UHI studies from various climate regions across the globe have been analysed by Wienert and Kuttler (2005).…”
Section: Urban Heat Islandmentioning
confidence: 99%
“…The section on Urban Heat Island Studies below provides a more detailed review and synthesis of some of the work including older studies. Locations of recent UHI studies include in (1) equatorial wet climates Singapore (Tso, 1996;Nicol, 1996Nicol, , 1998Goh and Chang, 1999;Chow and Roth, 2006); Kuala Lumpur (Tso, 1996), (2) tropical wet/dry climates Bangkok, Manila, Ho Chi Minh City (Hung et al, 2006), Mumbai (Kumar et al, 2001), Puerto Rico (Gonzalez et al, 2005;Velazquez-Lozada et al, 2006), (3) tropical highland climates Mexico City (Jauregui, 1997(Jauregui, , 2005Jauregui and Luyando, 1998), Guadalajara (Tereshchenko and Filonov, 2001), (4) subtropical humid climates Shanghai (Ding et al, 2002;Chen et al, 2003b), Hong Kong (Giridharan et al, 2004(Giridharan et al, , 2005Nicol and Wong, 2005) and Buenos Aires (Figuerola and Mazzeo, 1998;Bejaran and Camilloni, 2003) and (5) subtropical dry climates Pune (Deosthali, 2000), Tuscon (Comrie, 2000), Phoenix (Brazel et al, 2000;Hawkins et al, 2004 andFast et al, 2005), Cairo (Rooba, 2003), Ouagadougou (Linden, 2004) and Eilat (Sofer and Potchter, 2006). UHI studies from various climate regions across the globe have been analysed by Wienert and Kuttler (2005).…”
Section: Urban Heat Islandmentioning
confidence: 99%
“…An UHI has also been recorded in Singapore (Goh and Chang, 1999;Chow and Roth, 2006), where high atmospheric humidity and the frequent presence of low, warm clouds result in conditions that do not favor the development of rapid nocturnal cooling associated with heat islands in other climates. The development of an UHI when a new city is founded on a greenfield site, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A climate measurement in Athens, Greece showed that a clear increase in cooling rates can be observed when decreasing aspect ratios [57]. Goh and Chang [58] measured 17 estates in Singapore and conducted a correlation study between aspect ratio and nocturnal heat island intensities. Their statistical analysis results showed that the median aspect ratio can positively affect heat island intensities.…”
Section: Aspect Ratiomentioning
confidence: 99%